The face of the party? Leadership personalisation in British campaigns - Milazzo, Caitlin; Hammond, Jesse (Taylor & Francis, 2017)
The personal characteristics of political elites play an important role in British elections. While the personalisation of the media’s election coverage has been the subject of much debate, we know less about the conditions under which voters receive personalised messages directly from elites during the campaign. In this paper, we use a new dataset that includes more than 3,300 local communications from the 2015 general election to explore variation in the personalisation of campaign messaging. We find that there is systemic variation in terms of where photographs of party leaders are included in election communications, which provides further evidence that campaign messages are deployed strategically to portray the candidate – and their party – in the best possible light.